Ashes to eye: A skilled snake handler's experience with ophthalmic envenomation - Harry F. Williams; Karin Moejes; Jarred Williams; José R. Almeida; Ravi Savania; Subramanian Senthilkumaran; Ketan Patel; Sakthivel Vaiyapuri (Public Library of Science (PLoS), 2023)
With the continued growth of human populations, rural urbanisation and habitat degradation are on the rise, resulting in the displacement of native wildlife and an increase in human-wildlife conflicts. The presence of human habitation and waste often attracts rodents and thereby, snakes, leading to increased snake sightings in homes. To address this problem, snake handlers, who are volunteers that remove and relocate snakes away from human development areas, are called upon. However, snake removal is a high-risk task that poses a risk of envenomation, particularly when dealing with spitting snakes. Several cobra species have the ability to spit venom. If the venom enters a person's eye, it can result in ophthalmic envenomation, which can have serious consequences for their eyesight. Therefore, snake handlers should take precautions, wear suitable eye protection, and use appropriate tools to ensure their safety and that of the snake. In this case, an experienced snake handler was called to remove a spitting cobra, but they were ill-equipped. During the removal, the venom was sprayed across the handler's face, and some of it entered their eye, resulting in ophthalmic envenomation. The handler promptly irrigated their eye, but medical treatment was still necessary. This report highlights the risks and consequences of ophthalmic injury and the importance of wearing appropriate eye protection and taking due care when dealing with venomous species, particularly those that can spit venom. It serves as a reminder that accidents can happen at any time and experienced snake handlers are not exempt from the risks. Author summary The growth of human populations has led to an increase in rural urbanisation and habitat degradation. This, in turn, has displaced native wildlife and caused more conflicts between humans and wildlife. Human habitation and waste attract rodents and thereby, snakes, resulting in more snake sightings in homes. To deal with this issue, snake handlers/rescuers are asked to remove and relocate snakes away from human areas. However, snake removal is dangerous, especially when dealing with spitting snakes such as certain cobra species. These snakes can cause serious harm if their venom enters a person's eye, leading to ophthalmic envenomation. Therefore, snake handlers must take precautions by wearing appropriate eye protection and using suitable tools to ensure their safety and the snake's safety. Despite their experience, snake handlers are not exempt from the risks, as illustrated by a recent incident reported in this article where a handler was ill-equipped and suffered ophthalmic envenomation while removing a spitting cobra. This report emphasises the importance of taking due care when dealing with venomous species, particularly those that can spit venom, and wearing appropriate eye protection and using suitable tools to avoid accidents.